2003
DOI: 10.1074/jbc.m211044200
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Human Ether-à-Go-Go-related Gene (HERG) K+ Channel Function by Hypoglycemia and Hyperglycemia

Abstract: Hyperglycemia and hypoglycemia both can cause prolongation of the Q-T interval and ventricular arrhythmias. Here we studied modulation of human ether-à -gogo-related gene (HERG) K ؉ channel, the major molecular component of delayed rectifier K ؉ current responsible for cardiac repolarization, by glucose in HEK293 cells using whole-cell patch clamp techniques. We found that both hyperglycemia (extracellular glucose concentration Glucose, the primary end product of the digestion of glycogen, is essential for mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 51 publications
4
107
0
1
Order By: Relevance
“…Previous studies have reported that functional properties of hERG channels are altered by RS [14][15][16][17]41]. However, different effects on hERG channel functions were shown for different RS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that functional properties of hERG channels are altered by RS [14][15][16][17]41]. However, different effects on hERG channel functions were shown for different RS.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, involvement of cysteine oxidation is probable but it was not directly addressed. In contrast, the hERG channel function was impaired by RS that were generated by exposure to tumor necrosis factor-α and hyperglycemia [16,41]. There are several explanations for the observed different effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with congestive heart failure frequently have increased levels of catecholamines [68] and may be on inotropic agents, both of which cause Ca 2+ overload and increase the risk of sudden death. [72] showed that hypoglycaemia inhibits current through the human ether-a-go-go related gene channel, which generates I Kr , one of the main repolarising K + channels in human myocytes. Interestingly, the same team also showed that hyperglycaemia impairs current flow through the same channels, but by a different mechanism.…”
Section: The Two Proarrhythmic Mechanisms and Their Relevance To Hypomentioning
confidence: 99%
“…Избыток катехоламинов и гиперинсулинемия могут также вызвать гипокалиемию и увеличить внутриклеточную концентрацию кальция (Ca 2+). Это может привести к замедлению и асинхронизации процесса реполяризации в кардиомиоцитах, электрической негомогенности мио-карда и возникновению нарушений ритма сердца [19].…”
Section: потенциальные механизмы влияния гипогликемии на сердечнососunclassified